What colour is that sparrow? A case study: colour aberrations in the house sparrow "Passer domesticus" - Grouw, Hein van (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In this paper 16 distinct, heritable colour aberrations (mutations) in the House Sparrow are described, based on specimens found in museum collections, records of individuals seen in the wild and from bird breeders keeping aberrant coloured sparrows in captivity. Based on the frequency found in the museum specimens Brown is the most common mutation in the House Sparrow, followed by Ino and Albino.
Keywords: House Sparrows; Colour aberrations; Albino; Brown; Progressive Greying